Hydrothermally produced activated carbon spheres from discarded maize cobs for efficient removal of rose bengal dye from water environment - R. Sivaranjanee; P. Senthil Kumar; Gayathri Rangasamy (Desalination and Water Treatment)
This work used the subcritical water medium to create hydrothermally activated carbon spheres (HACs) from discarded maize cobs. As a form of adsorbent, the maize cob-produced HACs were used to remove Rose Bengal dye from aqueous solutions. Brunauer-Emmett-Teller (BET) surface area analysis, X-Ray diffraction (XRD), scanning electron microscopy (SEM), elemental analysis (EDX) and FTIR spectroscopy were used for analyzing the produced HACs. Assessing the influencing variables allowed for the optimization of the process of adsorption. The highest removal of dye happened at 60 min, sorbent dosage of 1 g/L, initial dye concentration of 100 mg/L and pH 3 as a consequence of the optimization procedure. The adsorption isotherms were studied using the Temkin, Freundlich and Langmuir models. For sorption of dye, Freundlich's model is the best model for the equilibrium data. The sorption of dye is shown by the pseudo first order, according to the kinetic investigations. Thermodynamic analyses demonstrated that sorption was an exothermic and spontaneous process. The evaluation of regeneration of spent HACs was conducted to determine their reuse ability. The results indicate that the regenerated HACs have a four-cycle lifespan.